Reserve carbohydrate metabolism in Saccharomyces cerevisiae: responses to nutrient limitation. - Lillie, S H (1980)
The amounts of glycogen and trehalose have been measured in cells of a prototrophic diploid yeast strain subjected to a variety of nutrient limitations. Both glycogen and trehalose were accumulated in cells deprived specifically of nirogen, sulfur, or phosphorus, suggesting that reserve carbohydrate accumulation is a general response to nutrient limitation. The patterns of accumulation and utilization of glycogen and trehalose were not identical under these conditions, suggesting that the two carbohydrates may play distinct physiological roles. Glycogen and trehalose were also accumulated by cells undergoing carbon and energy limitation, both during diauxic growth in a relatively poor medium and during the approach to stationary phase in a rich medium. Growth in the rich medium was shown to be carbon or energy limited or both, although the interaction between carbon source limitation and oxygen limitation was complex. In both media, the pattern of glycogen accumulation and utilization was compatible with its serving as a source of energy both during respiratory adaptation and during a subsequent starvation. In contrast, the pattern of trehalose accumulation and utilization seemed compatible only with the latter role. In cultures that were depleting their supplies of exogenous glucose, the accumulation of glycogen began at glucose concentrations well above those sufficient to suppress glycogen accumulation in cultures growing with a constant concentration of exogenous glucose. The mechanism of this effect is not clear, but may involve a response to the rapid rate of change in the glucose concentration.